Towards a Shariah compliance module for health care centres with reference to spiritual healers - Wan Muhammad, Ramizah (2016)
Generally, a good healthcare centre comprises of qualified manpower, right policies and right procedures in providing primary care, secondary care and tertiary care for the patients as well as in public health. Other than manpower, healthcare centres must also look at social, religion and cultural factors affecting the recipients of the healthcare services given by the healthcare centres. In this paper, the author will look at some pertinent issues such as the need to have spiritual healers in any healthcare centre to help the patients in dealing with fatal illness. The Spiritual healer is to help the patient and give him motivation so that he could have a positive mind throughout his journey in battling with his illness. Sometimes we have patient who refused to listen to the doctor's advice. Thus, the role of the spiritual healer would be important in assisting the healthcare centres and its management to convince him. Another issue is on privacy, respect and trust between patients and doctors as well as with the management of the healthcare centres. One of the duties of the healthcare centres’ management and doctors is, to respect the patient's religion and his faith. These three issues are amongst the important issues which every healthcare centre must look upon. Definitely there are a lot of challenges in addressing the above mentioned issues such as the procedures, methods on how to execute these issues and most importantly the perception of the public. In Islam, health care is one the five important elements in which the Prophet SAW has mentioned in one hadith to be taken care of. A study has shown that a nation building efforts has no meanings without the best public health and healthcare delivery system to the people.